Characterization of Interface and Bulk Traps in Ultrathin Atomic Layer-Deposited Oxide Semiconductor MOS Capacitors With HfO2/In2O3 Gate Stack by C-V and Conductance Method - Wang, Ziheng; Lin, Zehao; Si, Mengwei; Ye, Peide D. (Frontiers in Materials, 2022)
Oxide semiconductors have attracted revived interest for complementary metal-oxide-semiconductor (CMOS) back-end-of-line (BEOL) compatible devices for monolithic 3-dimensional (3D) integration. To obtain high-quality oxide/semiconductor interface and bulk semiconductor is critical to enhance the performance of oxide semiconductor transistors. Atomic-layer-deposited (ALD) indium oxide (In2O3) has been reported with superior performance such as high drive current, high mobility, steep subthreshold slope, ultrathin channel etc. In this work, the interface and bulk traps in the MOS gate stack of ALD In2O3 transistors are systematically studied by C-V and conductance method. A low EOT of 0.93 nm is achieved directly from the accumulation capacitance in C-V measurement, indicating a high-quality gate oxide and oxide/semiconductor interface. Defects in bulk In2O3 with energy levels in subgap are confirmed to be responsible to the conductance peak in GP/ω versus ω curves by TCAD simulation of C-V and G-V characteristics. A high n-type doping of 1×1020 /cm3 is extracted from C-V measurement. A high subgap density of states (DOS) of 3.3×1020 cm-3∙eV-1 is achieved from the conductance method, which contributes to the high n-type doping and high electron density. The high n-type doping furtherly confirms the capability of channel thickness scaling because charge neutrality level aligns deeply inside conduction band.